Peran Keberadaan Pasar Minggu Alon – Alon Kota Probolinggo terhadap Penambahan Penghasilan Para Pedagang Kaki Lima - H.M. Saiful Bahri; Muhammad Syarif Hidayatullah Elmas (Ecobuss, 2015)
This study aims to determine the role of Alon-Alon Mondays market against additional income Probolinggo City. This study used a qualitative approach with a sample of 50 respondents or 33% of all 150 merchants. The collection of data used in this study was to distribute questionnaires or questionnaires directly to the respondents. The results of these studies is how to show that the role of Alon-Alon Mondays market in Probolinggo City. The positive impact on the earnings of the hawkers, is very profitable for traders. It is shown from the respondents' answers as much as 24% to income above Rp. 400,000 every week, by 16% to 200,000 and 300,000 income and other income of less than 100,000 and 100,000. Keywords: Morning Market, additional income street vendors